Studies on the neuro-physiology of a free-living Platyhelminth - Boyle, Sheila A (Rhodes University, Faculty of Science, Department of Zoology, 1961)
From Resumé: The general picture of the physiology of invertebrate neuro-muscular systems as contrasted with the classical vertebrate system is presented and it is clear that one of the groups least investigated is the Phylum Platyhelminthes. An examination of the properties of the myo-neural system of a platyhelminth should be of interest, not only in itself, but also because of a possible relationship with the coelenterates, whose neuro-muscular system has been fairly extensively investigated. The aim of the present work was to determine some of the properties of the myo-neural system of a platyhelminth, and more especially those which would make possible a comparison with the myo-neural systems of other invertebrate phyla, and most particularly with the coelenterates. A preparation consisting of an entire decerebrate animal was used. The general anatomy of the musculature and basic plan of the nervous system are presented to facilitate an understanding of the experiments described, but a detailed examination of the relationships of nerves and muscles or of the innervation of the latter was not attempted. The spontaneous activity of such preparations was recorded kymographically and the characteristics of this activity under 'normal' conditions are described, together with observations on the effects on the normal spontaneous activity of treatments with sea waters of different ionic composition and with a number of drugs. The responses of the preparation to controlled electrical stimulation are also reported. The results are analysed and compared with the results of similar investigations on other invertebrate preparations, in particular the Anthozoa, and an interpretation of these results in terms of platyhelminth-coelenterate relations is discussed.
Keywords: Platyhelminthes